RIG012 assists in the treatment of pneumonia by inhibiting the RIG-I-like receptor signaling pathway - Zhang, Shi; Chen, Hanbing; Xie, Jianfeng; Huang, Lili (Frontiers in Medicine, 2024)
Objective Pneumonia is a common clinical condition primarily treated with antibiotics and organ support. Exploring the pathogenesis to identify therapeutic targets may aid in the adjunct treatment of pneumonia and improve survival rates. Methods Transcriptomic data from peripheral blood of 183 pneumonia patients were analyzed using Gene Set Variation Analysis (GSVA) and univariate Cox regression analysis to identify signaling pathways associated with pneumonia mortality. A pneumonia mouse model was established via airway injection of Klebsiella pneumoniae, and pathway-specific blockers were administered via tail vein infusion to assess whether the identified signaling pathways impact the mortality in pneumonia. Results The combination of GSVA and Cox analysis revealed 17 signaling pathways significantly associated with 28-day mortality in pneumonia patients (P < 0.05). Notably, the RIG-I-like receptor signaling pathway exhibited the highest hazard ratio of 2.501 with a 95% confidence interval of [1.223–5.114]. Infusion of RIG012 via the tail vein effectively inhibited the RIG-I-like receptor signaling pathway, significantly ameliorated lung injury in pneumonia mice, reduced pulmonary inflammatory responses, and showed a trend toward improved survival rates. Conclusion RIG012 may represent a novel adjunctive therapeutic agent for pneumonia.